The Federation house : Australia's own style - Fraser, Hugh, 1946- (New Holland, 2002)
Federation style housing is a unique and fascinating period of Australia's architectural history. Although the Federation house borrowed styles from many countries and eras, from English Queen Anne to Art Nouveau, it had a distinctive nationalistic flavour - God Save the Queen and Advance Australia Fair at the same time. This book is more than a mere series of pictures and descriptions. It gives advice to owners and would-be owners of Federation houses on how to restore them to their original glory, tips on specialised maintenance, and the names of experts who have the skills that may be needed.